Property rights and collective action in watersheds - Swallow, Brent M.; Johnson, Nancy L.; Knox, Anna; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2004)
According to the authors, watersheds define a terrain united by the flow of water, nutrients, pollutants, and sediment. Watersheds also link foresters, farmers, fishers, and urban dwellers in intricate social relationships. Both factors?the biophysical attributes and the policy and institutional environments?shape peoples? livelihoods and interactions within the watershed. In this brief the authors show that watersheds have such broad impacts at so many levels, they raise special issues for the management of resources through collective action. They explore the relationships between property rights, collective action, watershed management, and stakehold participation and conclude that empowering local communities to take a leading role in watershed management is essential. -- from Text.